Busulfan 12 mg/kg plus melphalan 140 mg/m2 versus melphalan 200 mg/m2 as conditioning regimens for autologous transplantation in newly diagnosed multiple myeloma patients included in the PETHEMA/GEM2000 study - Juan José Lahuerta; Maria Victoria Mateos; Joaquin Martínez-López; Carlos Grande; Javier de la Rubia; Laura Rosiñol; Anna Sureda; José García-Laraña; Joaquín Díaz-Mediavilla; Miguel T. Hernández-García; Dolores Carrera; Joan Besalduch; et al. (Haematologica, 2010)
Background The aim of this study was to compare the long-term safety and efficacy of oral busulfan 12 mg/kg plus melphalan 140 mg/m2 and melphalan 200 mg/m2 as conditioning regimens for autologous stem cell transplantation in newly diagnosed patients with multiple myeloma in the GEM2000 study.Design and Methods The first 225 patients received oral busulfan 12 mg/kg plus melphalan 140 mg/m2; because of a high frequency of veno-occlusive disease, the protocol was amended and a further 542 patients received melphalan 200 mg/m2.Results Engraftment and hospitalization times were similar in both groups. Oral busulfan 12 mg/kg plus melphalan 140 mg/m2 resulted in higher transplant-related mortality (8.4% versus 3.5%; P=0.002) due to the increased frequency of veno-occlusive disease in this group. Response rates were similar in both arms. With respective median follow-ups of 72 and 47 months, the median progression-free survival was significantly longer with busulfan plus melphalan (41 versus 31 months; P=0.009), although survival was similar to that in the melphalan 200 mg/m2 group. However, access to novel agents as salvage therapy after relapse/progression was significantly lower for patients receiving busulfan plus melphalan (43%) than for those receiving melphalan 200 mg/m2 (58%; P=0.01).Conclusions Conditioning with oral busulfan 12 mg/kg plus melphalan 140 mg/m2 was associated with longer progression-free survival but equivalent survival to that achieved with melphalan 200 mg/m2 but this should be counterbalanced against the higher frequency of veno-occlusive disease-related deaths. This latter fact together with the limited access to novel salvage therapies in patients conditioned with oral busulfan 12 mg/kg plus melphalan 140 mg/m2 may explain the absence of a survival difference. Oral busulfan was used in the present study; use of the intravenous formulation may reduce toxicity and result in greater efficacy, and warrants further investigation in myeloma patients. (Clinicaltrials.gov identifier: NCT00560053).